(untitled) (Journal of Enam Medical College, 2019)
Background: Cervical cancer remains a significant health burden worldwide. It is the second most commonly diagnosed cancer and third leading cause of cancer death among females in least developed countries. There were an estimated 527,600 new cervical cancer cases and 265,700 deaths worldwide in 2012. Bangladesh stands 11th in the world in cervical cancer fatalities with 17.9 women dying in 100,000 due to the largely sexually transmitted disease every year. Objective: The present study was done to evaluate the pattern of drug management, their adverse effects and socio-demographic characteristics of the patients of cervical carcinoma admitted and treated with chemotherapy in two tertiary care hospitals of Bangladesh. Materials and Methods: It was a cross-sectional observational study carried out from January to December 2015 at Dhaka Medical College & Hospital and National Institute of Cancer Research Hospital. During this period, 109 patients were selected by purposive sampling technique using a set of pre-tested structured questionnaire. Data analysis was done using SPSS version 21.0. Results: Most of the patients were in 5th decade (51.4%), from low (59.6%) income family and were married (98.16%). The mean duration of treatment for cancer was found 11.34 ± 5.32 months. Cisplatin (93.57%), 5 fluorouracil (63.3%) and paclitaxel (12.8%) were the most frequently prescribed drugs either alone or in combination. The adverse effects for cisplatin were gastrointestinal toxicity, nephrotoxicity, myelosuppresion and for 5-fluorouracil were myelosuppression, diarrhea, hyperpigmentation, dizziness, neuropathy, increased risk of infection. Conclusion: The combination of cisplatin and 5-fluorouracil was mostly (50.45%) prescribed followed by cisplatin alone (26.6%) to treat the patients of cervical carcinoma in Bangladesh. J Enam Med Col 2019; 9(2): 104-109